ChemInform Abstract: Zero Gap Alkaline Electrolysis Cell Design for Renewable Energy Storage as Hydrogen Gas. Issue 51 (5th December 2016) - Phillips, Robert; Dunnill, Charles W.
Abstract: Review: 43 refs.